Chinese endemic medicinal plant Bolbostemma paniculatum (Maxim.) Franquet: A comprehensive review - Zhou, Yujiao; Liu, Junyu; Zhang, Jianqiong; Xu, Yi; Li, Wangni; Gao, Pang; Xing, Yanghuan; Huang, Lehong; Qin, Xuhua; Jin, Shenrui (Frontiers in Pharmacology, 2022)
Bolbostemma paniculatum (Maxim.) Franquet is a unique species in China with a long history of medicinal use, which has the effects of detoxifying, dissolving lumps and dispersing swellings. And it is commonly used to treat many diseases, such as carbuncle and sore, acute mastitis, mammary cancer, scrofula and subcutaneous nodule traditionally. Modern clinical studies have found that B. paniculatum and its compounds can be used for the treatment of a variety of cancers, mastitis, hyperplasia of mammary glands, chronic lymphadenitis, cervical lymph tuberculosis and surgical wart skin diseases, and the curative effect is positive. At present, a variety of Chinese patent medicines containing B. paniculatum have been exploited and marketed in China for the treatment of cancers, breast diseases and flat warts. This review article comprehensively discussed the traditional application, botany, chemical components, pharmacological activities, and quality control of B. paniculatum, put forward some noteworthy issues and suggestions in current studies, and briefly discussed the possible development potential of this plant as well as future research perspectives. 96 compounds have been isolated from B.paniculatum, including triterpenoids, sterols, alkaloids and other components, of which triterpenoid saponins are the main bioactive components. The crude extracts and monomer compounds of B. paniculatum have a wide range of pharmacological activities, such as anti-tumor, antiviral, anti-inflammatory, immunoregulatory, and so on. Moreover, its anti-tumor mechanism involves many aspects, including inhibiting cell proliferation, promoting cell apoptosis, blocking the cell cycle, interfering with cell invasion and metastasis, suppressing angiogenesis, and regulating autophagy. While there is a lack of systematic and in-depth research on its anti-tumor active components and mechanism of action at the moment; and a tight connection between the chemical composition and pharmacological activity of B. paniculatum has also not been established. Besides, a systematic quality determination standard for B. paniculatum should also be built, in order to carry out further research.